2012
DOI: 10.1159/000334701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Omalizumab, an Anti-Immunoglobulin E Antibody, on Airway Wall Thickening in Asthma

Abstract: Background: Omalizumab may inhibit allergic inflammation and could contribute to decreasing airway remodeling in patients with asthma. Objective: The aim of this study was to assess the effects of omalizumab on airway wall thickness using computed tomography (CT). Methods: Thirty patients with severe persistent asthma were randomized to conventional therapy with (n = 14) or without omalizumab (n = 16) for 16 weeks. The following airway dimensions were assessed by a validated CT technique: airway wall area corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 84 publications
3
91
0
9
Order By: Relevance
“…The studies had a broad global representation, with 10 multi-national RCTs included [13][14][15][16][17][18][19][20][21][22] . The majority of included analyses evaluated patients aged 12 years and older (15 of 26 studies) [13][14][15][16][17][18]20,[22][23][24][25][26][27] ; five trials included adults, aged 18 years and older, only 21,[28][29][30][31] , and two trials included children aged 6 to <12 years 19,32 . The majority of RCTs were large (69% had n > 300 patients).…”
Section: Summary Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies had a broad global representation, with 10 multi-national RCTs included [13][14][15][16][17][18][19][20][21][22] . The majority of included analyses evaluated patients aged 12 years and older (15 of 26 studies) [13][14][15][16][17][18]20,[22][23][24][25][26][27] ; five trials included adults, aged 18 years and older, only 21,[28][29][30][31] , and two trials included children aged 6 to <12 years 19,32 . The majority of RCTs were large (69% had n > 300 patients).…”
Section: Summary Of Studies Includedmentioning
confidence: 99%
“…As shown in Table 4, adults with allergic asthma treated with omalizumab experienced improvements on the overall AQLQ score from baseline; the difference compared with placebo (and/or standard therapy for persistent severe asthma) was statistically significant in all but two studies 15,30 ; in these two studies, the change was numerically greater for omalizumabtreated patients, but statistical significance was not reported. 17,24 in the AQLQ scores of omalizumab-treated patients compared with placebotreated patients for the following: symptoms, activity limitation, and environmental exposure.…”
Section: Asthma-specific Quality-of-lifementioning
confidence: 99%
“…[36] noted inhibited production of TGF-b and pro-inflammatory cytokines (IL-4, IL-13 and TNF-a) by airway epithelial cells, stimulated by IL-1b and allergen. Hoshino et al [37] studied a clinical effect of omalizumab with regards to the remodelling process by using high-resolution CT (computed tomography) of the thoracic cavity. A follow-up examination performed after 16 weeks demonstrated thinner bronchial wall in patients with severe asthma, treated with omalizumab.…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 99%
“…Their expression is increased by IL-4 and IL-13 [91]. Omalizumab has been found to affect the production of these cytokines [8,9,37], thus it can potentially also influence eosinophil diapedesis.…”
Section: Mechanisms Of Omalizumab Effect On Eosinophilsmentioning
confidence: 99%
“…Recent studies have shown that long treatment with anti-IgE significantly reduced airway wall thickness and RBM thickness within 6 and 12 months, and this effect was independent of eosinophilic infiltration (21,22). Moreover, in another study, it was demonstrated that 48 weeks of treatment with omalizumab resulted in decrease in airway wall thickness as assessed by computed tomography (72).…”
Section: Discussionmentioning
confidence: 92%